Analisis Peningkatan Efisiensi Pada Produksi Rubber Step Dengan Metode Line Balancing Di Pt. Industri Komkar Indonesia - Luthfianto , Saufik; Edinov, Ewaldo Jales (Green Publisher Indonesia, 2025)
In the era of the Industrial Revolution 4.0, PT Industri Komkar Indonesia seeks to improve production efficiency. This research analyses and implements line balancing for production line optimisation. Data collection methods are carried out by observing cycle time, adjusting documents listed in the field, and interviews. The analysis results showed workload imbalance. Proposed line balancing improvements were designed to reduce idle time and work in process, and increase efficiency. This research contributes to the practice of production optimisation at PT Industri Komkar Indonesia and provides theoretical insights into the application of line balancing in manufacturing in Indonesia during the period of the 4.0 industrial revolution.